Genetic structure in the nonbreeding range of rufa Red Knots suggests distinct Arctic breeding populations - Verkuil, Y.I.; Tavares, E.; González, P.M.; Choffe, K.; Haddrath, O.; Peck, M.; Niles, L.J.; Baker, A.J.; Piersma, T.; Conklin, J.R. (Ornithological Applications, 2022)
An understanding of the migratory connectivity between breeding and nonbreeding areas is fundamental to the management of long-distance migrants under pressure from habitat change along their flyways. Here we describe evidence for genetic structure within the nonbreeding range of theendangered Arctic-Canadian rufa subspecies of Red Knots ( Calidris canutus ). Using blood and tissue samples from the major nonbreeding regions in Argentina (Tierra del Fuego and Río Negro), northern Brazil (Maranhão), and southeastern USA (Florida), we estimated genetic structure in 514 amplified fragment length polymorphism (AFLP) loci, applying cluster assignment analyses in DAPC, assignPOP , and STRUCTURE. Using a priori location information, individuals could be correctly re-assigned to their nonbreeding regions, which validated that the assignment accuracy of the data was sufficient. Without using a priori location information, we detected 3–5 genotype clusters, and posterior assignment probabilities of samples to these genotype clusters varied among the three regions. Lastly a chi-square test confirmed that allele frequencies varied significantly among nonbreeding regions, rejecting the hypothesis that samples were drawn from a single gene pool. Our findings hint at undescribed structure within the Red Knot rufa breeding range in the Canadian Arctic and indicate that each rufa nonbreeding area in this study hosts a different subsample of thesebreeding populations. The observation that nonbreeding sites of rufa Red Knots contain different genetic pools argues for separate conservation management of these sites.